1995
DOI: 10.2466/pr0.1995.77.3.727
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Situational Factors That Influence Managers' Ethical Judgments

Abstract: This study is an investigation of potential relationships between ethical judgments and both personal demographic and situational variables among a national sample of 602 managers. A significant positive relationship was found between education and ethical judgments of a scenario about an unethical situation. As formal education increased, managers tended to view unethical situations more favorably. Also, a significant negative relationship between size of a firm and ethical judgments of employees was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One reason for a lack of research on consumers' ethical beliefs may be that previous attempts to measure the ethical content of business situations have not generally predicted behavioral intentions very well Bass andHebert, 1995, Trevino andYoungblood, 1990. Recently, a multidimensional approach representing ethical/moral judgments (or moral construals) using three related dimensions has demonstrated significant relationships with future intentions across a wide variety of ethically charged settings (Robin et al, 1997).…”
Section: Marketing Ethicsmentioning
confidence: 99%
“…One reason for a lack of research on consumers' ethical beliefs may be that previous attempts to measure the ethical content of business situations have not generally predicted behavioral intentions very well Bass andHebert, 1995, Trevino andYoungblood, 1990. Recently, a multidimensional approach representing ethical/moral judgments (or moral construals) using three related dimensions has demonstrated significant relationships with future intentions across a wide variety of ethically charged settings (Robin et al, 1997).…”
Section: Marketing Ethicsmentioning
confidence: 99%
“…In view of previous research (e.g., Bass & Hebert, 1995), we believed that industry tenure could alter the managers' perceptions of many of the independent and dependent variables. Therefore, we controlled for industry tenure, measuring it in years as reported by respondents.…”
Section: Perceived Behavioral Control: Financial Costmentioning
confidence: 99%
“…When approached holistically, the study of ethical decision making is also cumbersome, because of the simultaneous influence of individual, situational, and issue-contingent forces (Bass & Hebert, 1995;Ford & Richardson, 1994;Jones, 1991;Morris, Rehbein, Hosseini, & Armacost, 1995;Trevifio, 1986). In this research, we sought to understand the diversity of influences shaping managers' environmental ethical decision intentions concerning the specific operational activity of hazardous wastewater treatment and centered our research around two questions: (1) What factors affect a manager's environmental ethical decision intention concerning the treatment of hazardous wastewater?…”
Section: As Shrivastava Noted In His Article "The Role Ofmentioning
confidence: 99%
“…However, studies addressing its relation to ethical judgment and behavior outline mixed findings. Some of these studies reported no significant differences between male and female with respect to their ethical judgment and conduct in negotiations (Bass et al 1995;Robin and Babin 1997;Westbrook et al 2011). Other studies supported the statement that men and women have different opinions about their acceptability of questionable negotiation tactics (Robinson, Lewicki and Donahue 2000).…”
Section: Gendermentioning
confidence: 91%